أنواع العلل الصرفية عند ابن السيّد البطليوسي ( 521هـ) - رواء سلمان ثجيل, الباحثة; أسعد عباس كاظم المياحيّ, ا.م.د. (لارك, 2024)
تناولت  في هذا البحث  أنواع العلل الصرفية عند ابن السيد البطليوسي، فابن السيّد البطليوسي يعتبر بالفعل من العلماء البارزين في العربية والأدب، وتعد مؤلفاته مصدرًا ثريًا للفهم العميق للعلوم اللغوية والأدبية. لقد قدم مساهمات كبيرة في توضيح العلل الصرفية وإصلاح الأخطاء اللغوية، وكانت له أثر كبير في تطور اللغة العربية في ذلك العصر وقد قامت الباحثة بتحليل الأنواع المختلفة للعلل الصرفية ودورها في تفسير وفهم النصوص  تم التركيز على أنواع العلل التي وردت في كتب ابن السيد البطليوسي والتي تتنوع بين النحو والصرف واللغة. وقد اشتمل البحث  على تعريف العلة لغةً واصطلاحاً، وتحدثت عن أهم أنواع العلل وقد تناولت دور العلل التعليمية والعلل التي تتطلب الإدغام والتخفيف. وقد قدمت مثالًا على كل نوع من هذه العلل وتم تفسيرها بشكل مفصل مع الاعتماد على النصوص الأصلية. وقد تم التركيز على مدى تأثير هذه العلل على فهم النصوص و الصيغ والمسائل الصرفيةTypes of morphological defects according to Ibn al-Sayyid al-Batalyusi (d. 521 AH) In this research, I discussed the types of morphological defects according to Ibn al-Sayyid al-Batalyusi. Ibn al-Sayyid al-Batalyusi is indeed considered one of the prominent scholars in Arabic and literature, and his works are a rich source for a deep understanding of linguistic and literary sciences. He made great contributions to clarifying morphological errors and correcting linguistic errors, and he had a major impact on the development of the Arabic language in that era. The researcher analyzed the different types of morphological errors and their role in interpreting and understanding texts. The focus was on the types of errors that appeared in the books of Ibn al-Sayyid al-Batalyusi, which varied. Between grammar, morphology and language. The research included the definition of the cause linguistically and terminologically. It talked about the most important types of causes and addressed the role of educational causes and the causes that require assimilation and alleviation. An example of each type of illness has been provided and explained in detail, relying on the original texts. Emphasis was placed on the extent to which these causes affect the understanding of texts, formulas, and morphological issue